2004
DOI: 10.1111/j.1471-0307.2004.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I‐converting‐enzyme‐inhibitory and antimicrobial bioactive peptides

Abstract: Bioactivities of peptides encrypted in major milk proteins are latent until they are released and activated by enzymatic proteolysis. After a brief description of the properties of some bioactive peptides, an overview of the angiotensin I‐converting‐enzyme (ACE)‐inhibitory and antimicrobial peptides is given. Emphasis is on the capacity of lactic acid bacteria to generate ACE‐inhibitory peptides and on the exploitation of the potential role of antimicrobial peptides derived from milk proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(158 citation statements)
references
References 100 publications
5
144
0
9
Order By: Relevance
“…bulgaricus possessed a more powerful proteolytic system than S. thermophilus. Gobbetti et al (2004) also reported that the type of lactic acid bacteria starter used is one of the main factors that influences the synthesis of hypotensive peptides in dairy products. The higher inhibitory activity can also be due to the composition of whey protein concentrate.…”
Section: Ace Inhibitory Activitymentioning
confidence: 99%
“…bulgaricus possessed a more powerful proteolytic system than S. thermophilus. Gobbetti et al (2004) also reported that the type of lactic acid bacteria starter used is one of the main factors that influences the synthesis of hypotensive peptides in dairy products. The higher inhibitory activity can also be due to the composition of whey protein concentrate.…”
Section: Ace Inhibitory Activitymentioning
confidence: 99%
“…During fermentation, many bioactive components are formed [34], as organic acids (lactic, pyruvic, formic, acetic and propionic), peptides derived from milk proteins due to proteolysis [16], and acetaldehyde, acetone, acetoin and biacetyl through carbohydrates degradation [20]. The CLA amounts could be enhanced through biohydrogenation of linoleic acid by bifidobacteria and other bacteria [24].…”
Section: Introductionmentioning
confidence: 99%
“…The unhydrolysed crude casein showed 13.5% ACE-inhibiting activity at 0.5 h, which increased to 19% after 4 h of hydrolysis because of the production of ACE-inhibiting peptides by the enzymatic activities of contaminating bacteria in the raw milk (Otte et al [17]) or by the endogenous enzymes of the milk (Gobbetti et al [18]). The 0.5 h and 4 h tryptic hydrolysates of the 10 kDa permeate showed 25.7% and 29.7% ACE inhibition, respectively.…”
Section: Ace-inhibiting Activity Of Crude Hydrolysates Formed By Trypsinmentioning
confidence: 99%
“…There was a steady increase in the cholesterol-reducing activity over time, with significant differences among the crude casein, the 1 kDa permeate, and the 10 kDa permeate. Unhydrolysed crude casein showed 23.2% cholesterol-reducing activity after 30 min hydrolysis, which increased to 39.5% after 4 h hydrolysis due to the release of bioactive peptides by the enzymatic activities of contaminating bacteria in the raw milk (Otte et al [17]) or by the endogenous enzymes of the milk (Gobbetti et al [18]). On the other hand, the 10 kDa permeate showed 44.9% cholesterol-reducing activity after 30 min hydrolysis, which is almost a twofold increase relative to that of the unhydrolysed crude casein.…”
Section: Tryptic Hydrolysis and The Rp-hplc Profile Of Caseinmentioning
confidence: 99%